Sustainable Development and Geographical Space : Issues of Population, Environment, Globalization and Education in Marginal Regions /: Issues of Population, Environment, Globalization and Education in Marginal Regions. ([2018]) - Jussila, Heikki; Majoral, Roser
No abstract available